Source orientation in human-computer interaction: programmer, networker, or independent social actor? - Sundar, S. Shyam; Nass, Clifford (Communication Research, 2000)
Two studies were conducted to examine whether individuals when they apply social rules and social expectations while working on a computer are interacting directly with the computer as an independent social actor or source or orienting to an unseen programmer or imagined person in another room. The findings revealed that, under different circumstances—in which individuals were told that they were dealing with computers and in a condition in which the individuals were told they were dealing with software programmers—differences in behavior surfaced. This indicates that individuals respond to the computer as an independent source of information.